THE GEN Z’s PREFERENCES IN CONSUMING TRADITIONAL FOOD - fitriana, widya; febriamansyah, rudi; nofialdi, nofialdi; evalia, nur afni; fairuzi, syofyan (AGROTEKSOS; Vol 35 No 3 (2025): Jurnal Agroteksos Desember 2025DO - 10.29303/agroteksos.v35i3.1514, 2025)
Traditional food plays a vital role in supporting agriculture and strengthening local industries, yet globalization and lifestyle changes have shifted consumer preferences. This study analyzes Gen-Z’s attitudes toward traditional food in Padang City, West Sumatra, a well-known culinary tourism destination. Using a qualitative approach, 185 Gen-Z consumers were interviewed through non-probability accidental sampling.Results indicate that 54.6% of respondents know how to prepare traditional food, with knowledge largely inherited from parents or family (70.5%). Consumption occurs several times a week (53.5%), most often with family (53.5%) and during cultural ceremonies (25.2%). Purchases are primarily made at food stalls or canteens (68.1%) and outlets (25.4%), rather than cafés or restaurants. Digital platforms are widely used for purchasing (59.4%), with Shopee (39.5%) and Go-Food (26.9%) being the most popular. The main reasons for consumption are authentic taste (50.8%) and affordable price (38.9%). Gen-Z expresses pride in consuming traditional food (52.9%) and a strong willingness to promote it (84.6%), though they also show a considerable tendency toward fast food (52.9%). Future efforts should emphasize food parenting, packaging innovation, and digital marketing to attract Gen-Z preferences and ensure the preservation of traditional culinary heritage.